Clustering of screen time behaviours in adolescents and its association with waist circumference and cardiorespiratory fitness. Issue 5 (May 2020) - da Costa, Bruno G.G.; Salmon, Jo; dos Santos, Priscila C.; Minatto, Giseli; Silva, Kelly S.
Abstract: Objectives: To identify the association of clusters of screen time (ST) behaviours with waist circumference (WC) and cardiorespiratory fitness (CRF) among adolescents. Design: Cross-sectional study of 574 adolescents (53% girls, 13 years), conducted in 2017. Methods: Waist circumference was measured, a shuttle run was performed to assess CRF, and a questionnaire was applied. Sex, age, socioeconomic status was reported, and daily duration of ST indicators for television viewing, computer use, videogame playing, and cellphone use, in weekdays and weekend days. Latent class analysis was performed to identify typologies of ST behaviours. Mixed-effects linear regressions were used to test the association of ST clusters with WC and CRF. Results: Participants' WC was 66.9 ± 8 cm and CRF was 39.5 ± 4 ml O2 /kg/min. Four clusters were identified: "Low ST" (25%); "High ST" (20%); "Gamers" (17%); and "High cellphone" (39%). No significant associations were found between ST clusters and WC. Maximum oxygen uptake was higher in those in the "Low ST" cluster compared to the other clusters. No significant interactions for sex were observed. Conclusions: Typologies of ST behaviours do not seem to be related to WC; however, those in the Low ST cluster had higher CRF compared to their peers in the other clusters, suggesting that total ST may be more important for CRF than specific indicators.